Transitioning to a Greener Labor Market : Cross-Country Evidence from Microdata - Bluedorn, John (IMF Working Papers; Working Paper ;, 2022)
This paper builds a new set of harmonized indicators of the environmental properties of jobs using micro-level labor force survey data from 34 economies between 2005 and 2019 and analyzes the labor market implications of the green economic transition and environmental policies. Based on the new set of indicators, the paper's main findings are that greener and more polluting jobs are concentrated among smaller subsets of workers, individual workers rarely move from more pollution-intensive to greener jobs, and workers in green-intensive jobs earn on average 7 percent more than workers in pollution-intensive jobs.